The effect of acute consumption of non-specific COX-inhibitors on neuromuscular fatigue and exercise performance - Morgan, P. (University of Exeter, 2019)
Exercise-induced fatigue is a complex, multifactorial process, the physiological bases of which are still widely debated. Recent research has implicated pain sensation in the aetiology of exercise-induced neuromuscular fatigue. Indeed, acute consumption of acetaminophen (ACT, or paracetamol), a non-specific inhibitor of the cyclooxygenase (COX) enzymes which synthesise prostaglandins and sensitise group III/IV muscle afferents, has been shown to improve exercise performance concomitant with a lower pain and effort sensation. However, the neurophysiological bases for the potential ergogenic effect of acute ACT ingestion, and how this influences the power/torque-duration relationship, have yet to be determined. Therefore, the purpose of this thesis was to assess the effect of acute consumption of the recommended therapeutic dose (1 g of ACT and 400 mg of IBP) of common pain-relieving, COX-inhibiting medicines on performance and the mechanisms of neuromuscular fatigue development in a variety of different exercise tests. Study 1: Mean torque (61?±?11 vs. 58?±?14% pre-exercise MVC) and end-test torque, reflective of critical torque, (44?±?13 vs. 40?±?15% pre-exercise MVC) were greater in the ACT trial compared to placebo (PL) when completing 60 maximum voluntary contractions (MVCs) of the knee extensors (both P < 0.05). Voluntary activation (VA; a marker of central fatigue) and potentiated twitch (pTw; a marker of peripheral fatigue) declined at a similar rate in both conditions (both P > 0.05). However, the decline in electromyography (EMG) amplitude, a marker of muscle activation, was attenuated in the ACT trial with EMG being greater compared to PL from 210 s onwards (P < 0.05). Study 2: Compared to PL, ACT ingestion increased end-test power, reflective of critical power (ACT: 297 ± 32 vs. PL: 288 ± 31 W, P < 0.001), and total work done (ACT: 66.4 ± 6.5 vs. PL: 65.4 ± 6.4 kJ, P < 0.05) without impacting W' (ACT: 13.1 ± 2.9 vs. PL: 13.6 ± 2.4 kJ, P > 0.05) or the M-wave amplitude (P > 0.05) during a 3-min all-out cycling test. EMG declined throughout the 3-min protocol in both the PL and ACT conditions; however, the decline in EMG was attenuated in the ACT condition, with the EMG amplitude being greater compared to PL over the last 60 s of the test (P < 0.05). Study 3: Time-to-exhaustion (Tlim) during severe-intensity knee extensor exercise in the right leg was 19% shorter after completing prior severe-intensity knee extensor exercise to exhaustion in the left leg following placebo ingestion (Leg2PL) compared to no prior fatigue in the left leg (Leg2CON) (Leg2CON: 385 ± 104 vs. Leg2PL: 311 ± 92 s; P < 0.05). ACT ingestion did not improve Tlim in the left leg without prior contralateral fatigue (Leg1ACT) compared to the placebo condition (Leg1PL) (Leg1CON: 396 ± 105 vs. Leg1PL: 390 ± 106 vs. Leg1ACT: 402 ± 101 s; P < 0.05). Moreover, ACT ingestion did not improve Tlim in the right leg following prior contralateral fatigue in the left leg (Leg2ACT) compared to the placebo condition (Leg2PL) (Leg2ACT: 324 ± 85 vs. Leg2PL: 311 ± 92 s; P > 0.05). There were no changes in intramuscular phosphorous substrates and metabolites, ratings of perceived exertion or EMG amplitude after ACT ingestion compared to PL ingestion in the severe-intensity single-leg knee extensor exercise tests completed with or without prior contralateral fatigue. Study 4: Mean torque (IBP: 60 ± 12 vs. PL: 58 ± 14% of pre-exercise MVC) and end-test torque (IBP: 41 ± 16 vs. PL: 40 ± 15% of pre-exercise MVC) were not different between the IBP and PL conditions when completing 60 MVCs of the knee extensors (P > 0.05). Similarly, end-test power output (IBP: 292 ± 28 W vs. PL: 288 ± 31 W) and work done (IBP: 65.9 ± 5.9 kJ vs. PL: 65.4 ± 6.4 kJ) during the 3-min all-out cycling tests were not different between the IBP and PL conditions (all P > 0.05). Neuromuscular fatigue markers developed at a similar rate in both exercise tests in the PL and IBP conditions (all P > 0.05). In conclusion, acute consumption of ACT, but not IBP, increased muscle activation and critical torque (and power), and attenuated fatigue development during maximal-intensity knee extensor and cycle ergometry exercise. However, acute ACT ingestion did not influence Tlim during continuous severe-intensity knee-extension exercise completed with or without prior fatigue of the contralateral limb. The original findings from this work suggest that acute ACT ingestion, but not IBP ingestion, might have implications for improving performance during maximal-intensity, but possibly not severe-intensity constant work rate exercise with these ergogenic effects linked to an increase in muscle activation. These findings offer insights into the potential for non-specific COX inhibitors to influence performance and neuromuscular fatigue development during different forms of exercise.